Packaging in the Function of Sustainable Development in Green Marketing Logistics - Nuševa, Danijela; Vukmirović, Goran (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
The aim of marketing logistics activities is to overcome the spatial and temporal differences between the production process and the product consumption process. Effective marketing logistics entails minimal product delivery costs according to customer requirements. By providing superior customer service, it contributes to increasing a company's competitive advantage. In addition to the positives, marketing logistics activities also produce effects that have a negative impact on the environment and sustainable development. Removal and reduction strategies and operations are an integral part of green marketing logistics. It is primarily aimed at harmonizing marketing logistics goals and sustainable development principles, focusing on areas such as: reducing greenhouse gas emissions, rational use of energy, recycling, waste management, etc. One of the areas is the concept of green packaging. Increasing consumer awareness, e-commerce development, digitalisation and other trends are pushing for a higher level of innovation and agility in the packaging industry to cope with pressure and potential threats. Green packaging, which is made entirely of natural materials and can be reused, promotes sustainable development at all stages of product life, does not damage the environment as well as human and animal health. The aim of this paper is to highlight its very important role in achieving sustainable development in green marketing logistics, which is reflected in the potential for its reuse, recycling or decommissioning.